TCPBP: Enhancing the TCP Throughput in High Speed Lossy Networks With a Single Mixed Routing Metric - Vilela, Hugo Christ; Fonseca, Keiko Verônica Ono; Fonseca, Mauro Sérgio Pereira (Anais do Simpósio Brasileiro de Redes de Computadores e Sistemas Distribuídos (SBRC); 2022: Anais do XL Simpósio Brasileiro de Redes de Computadores e Sistemas DistribuídosDO - 10.5753/sbrc.2022.222306, 2022)
In this work, we present Transmission Control Protocol Best Path (TCPBP), an alternative link-state routing metric aims to optimize single-path TCP throughput on intradomain High Speed Lossy Networks. The enhanced performance is achieved by combining delay and packet loss on a single mixed metric as a function parameter. In contrast, this function predicts the TCP throughput that should be maximized. As proof of concept, TCP bandwidth tests were executed in an SDN High Speed Lossy Network Linux-emulated topology with ten nodes, employing an intradomain link-state routing protocol (i.e., OSPF-like) capable of running both TCPBP and traditional metrics delay and hop-count. Such topology was chosen because of the potential to improve its TCP throughput with route selection, given the characteristics of the topology itself and the TCP throughput prediction model adopted. The overall TCP throughput performance obtained with TCPBP was greater than with different routes founded by traditional metrics, showing the potential of our proposal.